Occurrence and activity of Bemisia tabaci parasitoids on cassava in different agro-ecologies in Uganda - Otim, M.; Legg, James P.; Kyamanywa, S.; Polaszek, A.; Gerling, D. (Springer, 2005)
Bemisia tabaci Gennadius (Homoptera: Aleyrodidae) is the vector of cassava mosaic geminiviruses that cause cassava mosaic disease (CMD), which in turn causes devastating yield losses. Surveys were conducted from October 2000 to November 2001 in four agro-ecologies in Uganda to enhance the understanding of parasitoid fauna and parasitism of B. tabaci in cassava fields. Such an understanding is an essential prerequisite for the development of biological control methods of B. tabaci to complement current CMD control practices. Parasitoid abundance and parasitism efficiency varied between locations and sampling dates within the locations; highest parasitoid densities were observed at Namulonge in the Lake Victoria crescent while the lowest was at Kalangala. In all locations, parasitism was mainly due to Encarsia sophia Dodd and Girault and Eretmocerus mundus Mercet (all Hymenoptera: Aphelinidae). Two occasionally observed species included Encarsia mineoi Viggiani (Hymenoptera: Aphelinidae), only observed at Namulonge, and blackhead Encarsia (Hymenoptera: Aphelinidae) observed at Bulisa, Namulonge and Lyantonde. Parasitism efficiency was highest at Bulisa (57.9%), but ranged from 40.2 to 46.9% at the other three sites. This paper discusses the possible causes of variations in parasitoid abundance and parasitism efficiency, and proposes further studies that might be carried out to assess the potential for augmentation of parasitoids to control B. tabacipopulations and CMD.